ADVERSE EVENTS FOLLOWING IMMUNIZATION (AEFI) COVID-19 VACCINE IN TAPOS HEALTH CENTRE WEST JAVA - Siti Novy Romlah; Desy Darmayanti (LPPM STIKES BHAKTI HUSADA BENGKULU, 2022)
Introduction: In dealing with the Covid-19 pandemic, the Indonesian government made a regulation that all citizens who have met the requirements must vaccinate against Covid-19. There are moreover 27.6% of individuals who don't know whether to be immunized or not. Of the 7.6% of people who don't need to be immunized, 59% of them are uncertain of the security of the immunization, 43.17% of individuals are uncertain of the adequacy of the immunization, 24.2% are perplexed of side impacts, and 26% don't accept in antibodies (Sumartiningtyas, 2020). Purpose: The components that cause Post-Immunization Adverse Events (AEFI) for three days after immunization within the Tapos and Pamulang Health Centers. Research Strategy: Cohort study, the research was conducted by checking respondents who were given the CoronaVac vaccine of Covid-19 after by Adverse Events Following Immunization (AEFI) at the day and three days after immunization. Limitation: This inquire about did not see at variables beginning from immunization items, immunization quality, immunization procedural mistakes, and coincidental occasions that seem cause unfavorable occasions after Immunization. Contribution: The base for making choices almost Covid-19 immunization. Keywords: Age; Gender; History of being infected with Covid-19; Vaccine Status; Anxiety Level, AEFI at the day and three days after vaccine.